Stochastic simulation of climate parameters and potential productivity of maize using triangular distribution - Assis, Janilson Pinheiro de; Neto, Durval Dourado; Nass, Luciano Lourenço; Manfron, Paulo Augusto; Bonnecarrère, Reinaldo Antonio Garcia; Martin, Thomas Newton (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to simulate the potential productivity of maize, through Monte Carlo method, using an agrometeorological stochastic model. The experiment was conduct in Piracicaba, State of São Paulo, Brazil, at 22o42'30''S, 47o38'30''W, and 546 m altitude, the climate of the region is Cwa type, tropical humid. Daily average values of temperature (from 1917 to 2002) and global solar radiation (from 1978 to 2002) were used. Statistical performance index was used to compare observed and simulated data. The probabilistic models developed to simulate temperature and solar radiation averages produced similar values to observed data through triangular distribution, and it can be used in stochastic models to predict maize potential productivity in different dates of sowing.